Transitioning a multiethnic donor pool from serologic D-negative to molecularly RHD-negative at a hospital-based blood donor service - Willy A. Flegel; Kshitij Srivastava; Lorraine G. Caruccio; Pirmin Schmid; David A. Stiles; Marina U. Bueno; Nadine R. Dowling; Traci D. Paige; Sita Shrestha (Journal of Translational Medicine)
Abstract Background Some individuals carry a very low expression of the D-antigen, called a Del phenotype. Red cell units from such blood donors with DEL alleles are RhD protein-positive, despite being routinely labelled D-negative. Molecular typing offers a more sensitive method to identify Del individuals by detecting the presence of the RHD gene. Pools of 20 or more donor samples are routinely screened for the RHD gene in some, mostly European, donor populations. Methods A modular real-time PCR assay targeting RHD intron 4, exon 5, and exon 7 was developed for individual testing. We screened for the RHD gene among all blood donors who typed D-negative in routine serology. Results Over 15 years, 2254 D-negative donors were individually tested for the RHD gene. With a sensitivity of detecting 5 RHD positive gDNA copies per reaction, 42 donors tested positive (1.9%). Among them, 34 carried the common RHDΨ allele (80.9%), while 7 harbored 5 known RHD alleles, and 1 a novel RHD deletion. We inadvertently detected 2 other donors with DVI, establishing a population frequency of 1 in 731 for the U.S. Conclusions A modular approach for RHD screening is suitable for blood donors when sample pooling is not feasible among multiethnic donor populations. We transitioned donors since 2009 from serologic D-negative to molecularly RHD-negative status at the NIH Clinical Center. Molecular RHD screening of serologic D-negative donors is an effective way to identify individuals harboring DEL alleles that can cause alloimmunization in transfusion recipients.